Prevalence of hepatitis B and C seropositivity in pregnant women - Carla Natalina da Silva Fernandes; Michelly de Melo Alves; Michelly Lorrane de Souza; Gleyce Alves Machado; Gleiber Couto; Renata Alessandra Evangelista (SciELO, 2014)
The aim of the study was to identify the prevalence of hepatitis B and C seropositivity in pregnant women attended in a public maternity hospital located in Catalao-GO from 2005 to 2009. Descriptive, exploratory study conducted through patients` hospital records. For data analysis, we used SPSS version 18.0. The confidence interval (CI) was calculated using the Person χ² test, considering a significance level of 5% (p <0.05). The prevalence of HBV was 5.64% and HCV 0.098%, predominantly in young pregnant women aged between 20 and 30 years old, single and in their first pregnancy.